University teachers’ scientific research innovation incentive based on the three-party evolutionary game of the state, the colleges, and scientific researchers - Zheng, Yan (Frontiers in Psychology, 2023)
Scientific research in colleges and universities is of great significance to national innovation. Based on the evolutionary game theory, this paper constructs a theoretical model of the state, universities, and researchers. This paper also conducts numerical simulation on the model. The results reveal that when the scientific researchers’ success rate reaches a certain threshold, more and more scientific researchers will choose to invest in scientific research. Then, universities and the state will hold a long-term incentive attitude toward scientific research and scientific innovation. The study further found that the greater the success rate of researchers, the faster universities and the state will actively encourage scientific research.